Control and Empowerment of Abandoned Land for Agrarian Reform - Siti Hafsyah Idris; I Wayan Kartika Jaya Utama (Fakultas Hukum, Universitas Warmadewa, 2018)
This research is conducted to describe the impact of the issuance of Government Regulation Number 11 of 2010 on the Control and Utilization of Abandoned Land that serves as an important part of the agrarian reform agenda. It is relevant to the solution to counteract and eradicate the crisis of poverty by providing land and other facilities necessary for production so that people are able to work more productively and live a prosperous life. Essentially, it involves the whole process of restructuring the tenure, ownership, use, and utilization of land in order to achieve social welfare and justice. This research applies normative legal methods to conduct a literary review because of the characteristics and traditions of law. The approaches used in legal research are the statute approach, the case approach, and the conceptual approach. The results of the research show that agrarian reform needs to be included in the nation's agenda and the basic strategy of the country to build a just political, economic and social structure. This is the relevance of placing all references, understanding, scope, and usefulness of the management of